The Blackwell companion to science and Christianity - Stump, J. B.; Padgett, Alan G., 1955- (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2012)
This book provides a cutting-edge survey of the central ideas at play at the intersection of science and Christianity through 54 original articles by world-leading scholars and rising stars in the discipline.
Part VII. Christian bioethics. -- Shaping human life at the molecular level / James C. Peterson -- An inclusive framework for stem cell research / John F. Kilner -- The problem of transhumanism in the light of philosophy and theology / Philippe Gagnon -- Ecology and the environment / Lisa H. Sideris -- Part VIII. Metaphysical implications. -- Free will and rational choice / E.J. Lowe -- Science, religion, and infinity / Graham Oppy -- God and abstract objects / William Lane Craig -- Laws of nature / Lydia Jaeger -- Part IV. The mind. -- Christianity, neuroscience, and dualism / J.P. Moreland -- The emergence of persons / William Hasker -- Christianity and the extended-mind thesis / Lynne Rudder Baker -- In whose image? Artificial intelligence and the Imago Dei / Noreen Herzfeld -- How science lost its soul, and religion handed it back / Julian Baggini -- Part X. Theology. -- The Trinity and scientific reality / John Polkinghorne -- God and miracle in an age of science / Alan G. Padgett -- Eschatology in science and theology / Robert John Russell -- The quest for transcendence in theology and cosmology / Alexei V. Nesteruk -- Part XI. Significant figures of the twentieth century in science and Christianity. -- Pierre Teilhard de Chardin / James F. Salmon -- Thomas F. Torrance / Tapio Luoma -- Arthur Peacocke / Taede A. Smedes -- Ian G. Barbour / Nathan J. Hallanger -- Wolfhart Pannenberg / Hans Schwarz -- John Polkinghorne / Christopher C. Knight.
Includes bibliographical references and index.
Keywords: Religion and science; Religion and science; Religion; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Religion and science; Electronic books